Islandsk-tsjekkisk / Tsjekkisk-islandsk ordbok (IT/TI) - En biskopal, bidireksjonal ordbok i stort lommeformat - Haraldsson, Helgi (Nordiske Studier i Leksikografi, 2012)
The authors of the two-way Icelandic-Czech / Czech-Icelandic Dictionary are Helgi Haraldsson (Oslo) and Marta Bartošková (Prague). The estimated volume is about around 25,000 lemmas for each language. The dictionary is bidirectional in the sense that it is intended to be equally useful to both Czech and Icelandic users. This entails concise phonetics and morphology for both languages. Lemmas and equivalents are given codes that refer to the morphology, thus providing adequate information on inflection and conjugation. Particular attention is paid to syntax, especially valency and the like. Various devices are applied to save space and avoid unnecessary repetitions; this includes the use of ‘lexical sets’ as described by Bo Svensen in his Practical Lexicography (1993). Examples to elucidate the use of words in context are given insofar as space allows. (1003) Existing Icelandic-Czech and Czech-Icelandic lexicographic works are typically monodirectional and do not meet the needs of Icelandic users.